Supraspinatus tear: a mechanical outlet impingement lesion? : Prospective analysis of 100 patients with degenerative supraspinatus tendon tears - Bruttel, Jennifer; Loew, Markus; Sulzer, Susan; Lichtenberg, Sven; Schnetzke, Marc (Obere Extremität, 2021)
Abstract - Background - The etiology of degenerative supraspinatus tendon (SSP) tear is still subject to discussion. - Objectives - Our objective was to correlate clinical, radiological, and intraoperative signs of mechanical outlet impingement in patients with degenerative SSP tears. - Materials and methods - This prospective study included 100 patients with degenerative SSP tears that required surgery. Preoperatively, clinical impingement signs and radiological parameters (critical shoulder angle [CSA], acromion type according to Bigliani, acromion index [AI]) were recorded. Intraoperatively, the extent of the rupture and grinding marks on the bottom of the acromion were assessed. - Results - Of the 100 patients, 59 had clinical impingement signs preoperatively; 90 patients had at least one positive radiological sign (CSA >35°, AI >0.67, acromion type II or III). In 23 patients a partial tear, in 55 patients a full thickness tear, and in 22 patients an additional infraspinatus tendon tear were found. In 10 cases no grinding marks at the bottom of the acromion during arthroscopy were found. In 75 cases moderate grinding marks and in 15 cases severe marks with bare bone at the bottom of the acromion were found. There was no statistically significant correlation between preoperative impingement signs and arthroscopic grinding marks ( - p - = 0.83) or between clinical signs and radiological parameters ( - p - = 0.44). There was no significant correlation between extent of the rupture, extent of grinding marks or radiological impingement parameters ( - p - = 0.16; - p - = 0.26). - Conclusion - We could not verify a correlation between clinical and radiological impingement sign and arthroscopic impingement parameters. Based on our study, degenerative SSP tear cannot be characterized as the result of a mechanical outlet impingement. - Zusammenfassung - Hintergrund - Die Ätiologie der degenerativen Supraspinatussehnen(SSP)-Ruptur ist immer noch Gegenstand der Diskussion. Fragestellung - In dieser Studie wurde die Frage untersucht, ob es einen Zusammenhang zwischen klinischen, radiologischen und intraoperativen Zeichen eines mechanischen Outlet-Impingements bei Patienten mit degenerativer SSP-Ruptur gibt. - Material und Methodik - In dieser prospektiven Studie wurden 100 Patienten mit operationswürdiger SSP-Ruptur einbezogen. Präoperativ wurden klinische Impingementzeichen sowie radiologische Parameter (kritischer Schulterwinkel, CSA; Akromiontyp nach Bigliani; Akromion-Index, AI) erfasst. Intraoperativ wurden das Ausmaß der Ruptur (nach Bateman) sowie das Ausmaß der Schliffspuren an der Unterseite des Akromions erfasst. - Ergebnisse - Präoperativ wiesen 59 von 100 Patienten positive Impingementzeichen auf. Mindestens ein positives radiologisches Zeichen lag bei 90 Patienten vor (CSA >35°, AI >0,67; Akromiontyp II oder III). Bei 23 Patienten zeigte sich intraoperativ eine partielle SSP-Ruptur und bei 55 Patienten eine transmurale SSP-Ruptur. Eine 2‑Sehnen-Ruptur bestand bei 22 Patienten. In 10 Fällen waren keine Schliffspuren am Akromion sichtbar, in 75 Fällen moderate Schliffspuren, und in 15 Fällen lag der Knochen an der Akromionunterfläche frei. Es zeigte sich kein statistisch signifikanter Zusammenhang zwischen positiver Impingementsymptomatik und Schliffspuren am Akromion ( - p - = 0,83) oder zwischen positiver Impingementsymptomatik und den radiologischen Parametern ( - p - ≥0,44). Ein Zusammenhang zwischen Rupturgröße und Schliffspuren oder den radiologischen Parametern war ebenfalls nicht festzustellen ( - p - = 0,16; - p - = 0,26). - Schlussfolgerung - Es ließ sich kein Zusammenhang zwischen klinischen und radiologischen Impingementzeichen und intraoperativen Befunden nachweisen. Daher lässt sich auf dem Boden der vorliegenden Ergebnisse die SSP-Ruptur nicht als Folge eines mechanisches Outlet-Impingements darstellen.
Gesehen am 12.06.2023